Modelling the interplay between childhood and adult adversity in pathways to psychosis: initial evidence from the AESOP study. Issue 2 (January 2014) - Morgan, C.; Reininghaus, U.; Fearon, P.; Hutchinson, G.; Morgan, K.; Dazzan, P.; Boydell, J.; Kirkbride, J. B.; Doody, G. A.; Jones, P. B.; Murray, R. M.; Craig, T.
<x content-type="archive" xml:space="preserve">Abstract</x> Background There is evidence that a range of socio-environmental exposures is associated with an increased risk of psychosis. However, despite the fact that such factors probably combine in complex ways to increase risk, the majority of studies have tended to consider each exposure separately. In light of this, we sought to extend previous analyses of data from the AESOP (Aetiology and Ethnicity in Schizophrenia and Other Psychoses) study on childhood and adult markers of disadvantage to examine how they combine to increase risk of psychosis, testing both mediation (path) models and synergistic effects. Method All patients with a first episode of psychosis who made contact with psychiatric services in defined catchment areas in London and Nottingham, UK (n = 390) and a series of community controls (n = 391) were included in the AESOP study. Data relating to clinical and social variables, including parental separation and loss, education and adult disadvantage, were collected from cases and controls. Results There was evidence that the effect of separation from, but not death of, a parent in childhood on risk of psychosis was partially mediated through subsequent poor educational attainment (no qualifications), adult social disadvantage and, to a lesser degree, low self-esteem. In addition, there was strong evidence that separation from, but not death of, a parent combined synergistically with subsequent disadvantage to increase risk. These effects held for all ethnic groups in the sample. Conclusions Exposure to childhood and adult disadvantage may combine in complex ways to push some individuals along a predominantly sociodevelopmental pathway to psychosis.